Program Kemitraan Masyarakat untuk Peningkatan Sistem Penyediaan Air Minum Pada Masyarakat Di Desa Pinenek Kecamatan Likupang Timur Kabupaten Minahasa Utara : Community Partnership Program to Improve Drinking Water Supply System in Pinenek Village, East Likupang District, North Minahasa Regency (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Pinenek Village has an area of 4025 Ha and the village is located about 25 km from the Government Center of East Likupang District. This community service program aims to improve the drinking water supply system (SPAM) for the community in Pinenek Village, Likupang District, North Minahasa Regency. The availability of adequate clean water is a basic need that is very important to improve the quality of life of the community.  However, there are still various problems in the provision of drinking water, such as lack of access to clean water sources and lack of public understanding regarding sustainable water management and utilization. Through this program, the optimization of the water supply system is carried out with a technical and participatory approach that includes improving the distribution network, increasing capacity, storing water, and educating the community about the importance of clean water management. The methods used include field surveys, and socialization for local communities. The results of this activity show an increase in access to drinking water that is cleaner and suitable for consumption, as well as increased community awareness in maintaining and managing water resources.With this program, it is hoped that the sustainability of the drinking water supply system in Pinenek Village can be maintained so that it can support community welfare and improve the quality of environmental health as a whole.